1996
DOI: 10.1002/chin.199630141
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Antimicrobial Activity of 1,5‐Diaryl‐3‐hydroxy‐2‐oxo‐3‐ pyrroline‐4‐carboxylic Acids and Their Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For example, some investigations showed that they have good antimicrobial activity [9][10][11][12]. Also, these compounds have many other biological activities such as anti-inflammatory, antiviral, antifungal, and nootropic [13][14][15]. To sum up, various biologically active natural products containing either 3-acyl-5-hydroxy-3-pyrrolin-2-one or 3acyl-3,4-epoxy-5-hydroxypyrrolidin-2-one are isolated, suggesting that the pyrrolidinone moiety is mostly responsible for the biological activity of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some investigations showed that they have good antimicrobial activity [9][10][11][12]. Also, these compounds have many other biological activities such as anti-inflammatory, antiviral, antifungal, and nootropic [13][14][15]. To sum up, various biologically active natural products containing either 3-acyl-5-hydroxy-3-pyrrolin-2-one or 3acyl-3,4-epoxy-5-hydroxypyrrolidin-2-one are isolated, suggesting that the pyrrolidinone moiety is mostly responsible for the biological activity of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Many biologically active compounds, potent pharmaceuticals, and natural products contain the pyrrole structural motif [1]. Among the pyrrole derivatives, dihydro-2-oxoypyrroles show such versatility and they are important substructures in a variety of pharmacy, including products active against viral infections (HIV [2,3], influenza [4] cytomegalovirus [5]), anticancer agents [6] and products active against microbiological diseases [7][8][9] (bacterial or fungal). Furthermore, dihydro-2-oxoypyrrole derivatives have been used as PI-091 [10], which is a novel platelet aggregation inhibitor, and EBPC, which is a highly specific aldose reductase inhibitor [11], as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of active substances containing the quinoline ring within their structure is used in medicine, such as chloroquine (immunosuppressive, anti-inflammatory, antimalarial action), quinidine (an antiarrhythmic agent), echinopsine (a general stimulant), nitroxoline (5-Nok, antibacterial), fluoroquinolones (antibacterial action) [2,3]. Compounds with both growth stimulating and growth suppressing activity on certain plants have been identified in the quinoline series [4].It has previously been shown that the interaction of 4-acyl-5-aryl-3-hydroxy-3-pyrrolin-2-ones with binucleophiles can produce a plethora of fused heterocyclic ring systems: pyrrolo [3,4-c]pyrazol-6-ones [5, 6], pyrrolo[3,4-f][1,4]diazepines [5], pyrrolo[3,4-c]pyrimidines [7, 8], pyrrolo[2,3-b]quinoxalines [9, 10], pyrrolo[3,4-b][1,5]benzodiazepines [11], 3,4-dihydroquinoxalin-2(1H)-ones [12]. It has also been found that 3-aryl-5-arylamino-4-benzoyl-1H-3-pyrrolin-2-ones by brief heating with concentrated H 2 SO 4 followed by keeping the reaction mixture at room temperature for long periods undergo intramolecular cyclization to form 5(7)-R-1-aryl-9-phenylpyrrolo[3,4-b]quinolin-3-ones [13].…”
mentioning
confidence: 99%
“…It has previously been shown that the interaction of 4-acyl-5-aryl-3-hydroxy-3-pyrrolin-2-ones with binucleophiles can produce a plethora of fused heterocyclic ring systems: pyrrolo [3,4-c]pyrazol-6-ones [5, 6], pyrrolo[3,4-f][1,4]diazepines [5], pyrrolo[3,4-c]pyrimidines [7, 8], pyrrolo[2,3-b]quinoxalines [9, 10], pyrrolo[3,4-b][1,5]benzodiazepines [11], 3,4-dihydroquinoxalin-2(1H)-ones [12]. It has also been found that 3-aryl-5-arylamino-4-benzoyl-1H-3-pyrrolin-2-ones by brief heating with concentrated H 2 SO 4 followed by keeping the reaction mixture at room temperature for long periods undergo intramolecular cyclization to form 5(7)-R-1-aryl-9-phenylpyrrolo[3,4-b]quinolin-3-ones [13].…”
mentioning
confidence: 99%